Nutritional Value of Some Newly Introduced and Tested Forage Plants in the Southeastern Regions of Algeria - khedidja djennane; Deghnouche Kahramen; Chehma Abdelmadjid (Al-Qadisiyah Journal For Agriculture Sciences, 2022)
In Algeria, the high prices of animal products are due to the cost of food, itself linked to the lack of food resources.A fodder deficit really exists, it is urgent to remedy it by relaunching new varieties adapted to our pedoclimatic conditions to cover the needs of farm animals throughout the year. It is in this context that our study takes place, the objective of which is to appréciate the nutritional value of fodder plants newly introduced and tested in the Algerian south-east, the region ofBiskra, it is about the two plants; Panicum maximum from the Poaceae family and Sesbania aculeata from the Fabaceae family. The determination of the chemical composition of these plants revealed significant energy and nitrogen values. It appears that panicum presents the highest values in CC, MM, ADF and NDF (37.60%, 17%, 55.32% and 70.54%, respectively).The study of CPArevealed that sesbania is in the same group with lucerne which makes it a food of good nutritional quality with energy values of UFmeat and UFmilk (1.04 and 1.01) and nitrogen values PDIE and PDIN (111.84 and 101.63) , respectively the highest.